Desain Model Pembelajaran CORE (Connecting, Organizing, Reflecting, Extending) Pada Mata Kuliah Kewirausahaan Berbasis Ekonomi Digital - Menik Kurnia Siwi; Tri Kurniawati (Jurnal Pendidikan Ekonomi, 2021)
This study aims to produce a CORE learning model design ( Connecting, Organizing, Reflecting, Extending) in entrepreneurship course based on the digital economy. This research used research and development method with ADDIE  (Analysis, Design, Development, Implementation, and Evaluation) model. This research was conducted at Padang State Unversity. The model validation test is carried out by experts and shows that this model is suitbale for use. The practicality test results show that this model is 87,33% very practical to use and the test results show that student learning outcomes improve and students can give a positive response. DOI: https://dx.doi.org/10.17977/UM014v14i12021p77